Comparative Analysis of PEG-3000 Precipitated Proteins From Cold-Acclimated and Non-Acclimated Tenebrio molitor Larvae - Gulevsky, Oleksandr K.; Gryschenkova, Olena O.; Relina, Liana I.; Tretiak, Diana V. (Problems of Cryobiology and Cryomedicine, 2015)
N/A Probl Cryobiol Cryomed 2015; 25(1):76-80.